Transnational governmentality in the context of resource extraction (with Suzana Sawyer), in the politics of resource extraction: indigenous peoples, corporations and the state - Gomez, E.T.; Sawyer, S. (Palgrave-Macmillan, 2012)
International institutions, including the United Nations and World Bank, and numerous multinational companies (MNCs) have voiced concern over the adverse impact of resource extraction activities on the livelihood of indigenous communities. Yet the scale and scope of problems confronting indigenous peoples caused by mineral extraction projects endorsed by governments, international agencies and MNCs is monumental. This raises a paradox: Despite the burgeoning number of international charters and national laws asserting the rights of indigenous peoples, they find themselves subjected to discrimination, dispossession and racism. The authors explore this paradox by examining mega resource extraction projects in Australia, Bolivia, Canada, Chad and Cameroon, India, Nigeria, Peru and the Philippines.